The state of sustainability disclosure and effect on companies' financial performance - Mohd Said, Ridzwana; Lim, Theng Theng; Senik, Rosmila; Yusri, Yusniyati; Ong, Tze San (Universiti Putra Malaysia Press, 2015)
In Malaysia, the disclosure of sustainability information is lacking since it is not a common practice for companies in this country compared to developed countries. Sustainability disclosure consists of three dimensions, namely, economic, environmental and social disclosure. This study examined the extensiveness of sustainability disclosure in terms of quality and quantity. In addition, the relationship between sustainability disclosure and financial performance, which was measured by return on assets (ROA) and earnings per share (EPS), was also investigated. The annual reports and stand-alone reports from 2007 to 2010 of 24 public companies listed on Bursa Malaysia (Malaysian Stock Exchange) participated in the ACCA Sustainability Reporting Awards (MaSRA) were analysed using content analysis. Meanwhile, the signalling hypothesis was used to address the relationships of the variables. It was found that the quantity of sustainability disclosure increased from year to year with the highest number of sentences of disclosure in the social dimension. In addition, companies provided comprehensive disclosure in the economic dimension in the forms of qualitative, monetary and non-monetary. Using multiple regression analysis, the results revealed no relationships between the sustainability dimensions and the financial performance of companies except for the economic dimension and ROA with negative effect. The present study contributes to the current literature on sustainability, particularly inasmuch as prior studies mainly focus on corporate social reporting issues.